Joe Hamilton - unknown:::Creator::::::::::::
Joe Hamilton (left) walking with man. Joe Hamilton was John Steinbeck's uncle, a successful man with the connections to get Steinbeck a job on the newspaper The New York American. Hard copy is photocopy.